Gestión automática para la solicitud de pedidos a través de aplicaciones de mensajería en establecimientos comerciales como Gastrobares. - Rodríguez Gamboa, Diego Alejandro; Rodríguez Gamboa, Sandra Yamile (Universidad Antonio Nariño, 2022)
Today the differentiator component between companies is the service and the value that this implies in the immediate response to present these services and products to their clients in a timely and agile manner in order to always keep them satisfied. This is where technology begins to play a very important role in providing more efficient and effective services , with immediate and concrete responses. This technology every day offers us more and better opportunities for development by implementing techniques such as the use of artificial intelligence, training of neural networks, using the most widely used commun ication tools worldwide and by combining these three we can offer companies that in this case allows to the Gastrobars to have efficient, timely, agile and effective communication with their customers when doing order or requesting their billing.